Association of Hypothyroidism with Metabolic Syndrome - Fakhra Noureen , Muhammad Nadeem Akbar Khan , Abid Saeed khan , Shazia Qayyum , Aqsa Liaquat (Journal of Islamic International Medical College, 2018)
Objective: To determine the association between hypothyroidism and metabolic syndrome Study Design: Observational cross sectional study Place and Duration of Study: Data was collected from Medical unit and Department of Pathology, Pakistan Railways Hospital, Islamic International Medical College, Rawalpindi and Capital Hospital Islamabad from April 2017 to April 2018. Materials and Methods: One hundred and fifty adult subjects participated in this study. Hundred hypothyroid subjects were recruited as cases on the basis of laboratory findings of raised serum thyroid stimulating hormone (TSH) levels and low serum free thyroxine (FT4) level. Newly diagnosed/ untreated cases of Hypothyroidism and adults of either sex were included. After an overnight fasting, participants were tested for various components of metabolic syndrome. Fifty euthyroid subjects were taken as controls. Data was analyzed by SPSS-21. Results: Among 150 total recruited subjects, 25% hypothyroid cases and 10% euthyroid controls were diagnosed with metabolic syndrome. These results were statistically significant with p value 0.030. Mean serum triglycerides 183 ±26 and 153±26 mg/dl and mean fasting blood glucose 100 ±30 and 96 ±18 mg/dl respectively among hypothyroid and euthyroid patients were significant with p-value 0.001. Whereas, waist circumference, high density lipoprotein cholesterol and blood pressure measurement of hypothyroid and euthyroid individuals were not significant. Conclusion: Hypothyroidism is associated with various components of metabolic syndrome.